Controversial clinical practices for patients with preeclampsia or HELLP syndrome: a survey - Basaran, Ahmet; Basaran, Mustafa; Basaran, Betul; Sen, Cihat; Martin, James N. (Journal of perinatal medicine, 2015)
Considerable controversy continues to surround the management of severe preeclampsia and HELLP syndrome. Experts, researchers, and those published in the field were surveyed about their specific practices. An extensive literature search was undertaken to identify the cohort of authors with recent publications on the subjects of preeclampsia (2009–2012) and HELLP syndrome (2005–2012). Online surveys were sent to all authors using the email addresses found in their publications. Surveys were delivered by email to 363 authors of preeclampsia publications and 91 authors of HELLP syndrome publications. Completed surveys were received from 61 (13.4%) of the group. Except for consensus about the indication of corticosteroids for the enhancement of fetal lung maturation, there was considerable variation in corticosteroid practice and anesthesia techniques. A marked diversity in practice characterized the clinical care rendered by experts in the field of preeclampsia and HELLP syndrome. Thus, there is an urgent need for well-designed and executed prospective clinical trials to improve the evidence for best consensus practice in this area of obstetrical medicine.